Green insurance: A roadmap for executive management - Lukas Stricker; Carlo Pugnetti; Joël Wagner; Angela Zeier Röschmann (Journal of Risk and Financial Management, 2022)
Anthropogenic climate change is accelerating, and severe and widespread consequences are expected in many areas. Although the insurance sector is not closely associated with any of the sustainability dimensions, expectations may change rapidly. Against this background, we analyze the role of insurers, especially in the property and casualty areas, in addressing the environmental and climate risk challenges and developing a truly sustainable, environmentally friendly business model-green insurance. Building on the Principles of Sustainable Insurance set by the United Nations, we develop a comprehensive roadmap along the insurance value chain for executive management to design their company's sustainability efforts, with special focus on property and casualty. The roadmap indicates actions to be taken as well as metrics to be managed in product development, marketing and sales, risk management and underwriting and operations and claims management towards green insurance. The existing products, risk appetite and operational processes must be reviewed to support sustainability goals and include the full portfolio of activities, including claims. The time to act is now, the sustainability journey is complex and the proposed business model transformation should provide benefits for early movers.
Keywords: 650; sustainability; green insurance; insurance management; value chain